Meningkatkan Kemampuan Mengenal Warna Melalui Metode Eksperimen Pada Anak Usia Dini di Paud Gmim Pniel Bahu - Threesje Tolukun (Peneliti.net, 2022)
This study aims to improve the ability to recognize colors through experimental methods in early childhood at PAUD GMIM Peniel Bahu. With the experimental method there is direct involvement of children so that children gain direct experience in the learning process. This type of research is collaborative classroom action research. Collaborative classroom action research is the researcher collaborates with the classroom teacher in carrying out the research. This study uses a classroom action research model and refers to the implementation process proposed by Kemmis and Mc. Taggart. The subjects in this study were children aged 3-4 years consisting of 9 girls and 7 boys. The data collection method used is an observation sheet (check list). The data analysis technique was carried out quantitatively. The results showed that the ability to recognize colors can be increased by the experimental method. As for the learning process, children are given the opportunity to experiment with colors that are simple and interesting for children. The results of the study increased gradually, this can be seen from the data from observations in Pre-action, Cycle I and Cycle II. The average percentage gain in Pre-action was 45.31%, increased in Cycle I with a percentage of 66.48% and increased to 86.97% in Cycle II.